An evaluation of solid carbon dioxide (CO2) blasting as a cleaning method to remove soot from textiles after smouldering fire and fire, with the possibility to transfer the method to historical textiles within a museum context - Mari Grønlund (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The main issue for the master dissertation was to evaluate if solid carbon dioxide (CO2) blasting as a cleaning method could be used to remove soot from textiles after smouldering fire, with the possibility to transfer the method to historical textiles. The experiments in the thesis were carried out with textile dummies. From the results, it was concluded the method in itself showed a potential, but the cleaning equipment was not appropriate.